Microencapsulated Microbial Seed Coating Could Improve Soil Environment and Maize Grain Yield in Saline Soil - Qiuyan Huo; Min Gong; Yawen Jiang; Xi Yang; Meng Kong; Jiuxing He; Qiang Zhang; Jiqing Song; Xinzhu Li; Wei Han; Xurong Mei; Guohua Lv (Plants)
Soil salinization is one of the major challenges for modern agriculture, posing a great threat to soil health and food security. Field experiments were conducted to evaluate the effect of seed coating on soil environment and maize growth in saline soils. Three treatments were applied to maize seeds: coating with a microencapsulated microbial agent (ME), coating with microbial only (MB), and no coating (CK). High-throughput sequencing of soil bacterial and fungal 16S and ITS rRNA genes was performed using the Illumina HiSeq platform to analyze the effects of these treatments on soil bacterial and fungal diversity and community structure. Additionally, the influence of different treatments on endogenous hormones and yield of maize were investigated. It was found that the coating with a microencapsulated microbial agent led to decreases in pH and electrical conductivity (EC), while increasing the content of soil available phosphorus. This coating improved soil microbial diversity, significantly increasing the relative abundance of the main bacteria genera, Bacillus (34.9%), and the main fungal genera, Mortierella (190.4%). The treatment also significantly enhanced indole-3-acetic acid (IAA) by 51.2%, contributing to improvements in resistance to salt stress. The germination rate increased by 22.9%, the 100-grain weight increased by 12.7%, and grain yield increased by 14.3%. The use of the microencapsulated microbial agent effectively mitigated the adverse effects of salt stress on maize plants. This approach is beneficial for promoting sustainable agriculture in saline soils.